Serosurvey of mountain lions in southern Arizona - Kerry L. Nicholson; Ted H. Noon; Paul R. Krausman (Wildlife Society Bulletin)
Abstract An understanding of the prevalence of diseases in free‐ranging populations of felids is limited, and there is even less known about the overall health and diseases of wild felids that inhabit or utilize urban areas. We collected serum samples from 9 radiocollared mountain lions (Puma concolor) in the mountains surrounding Tucson, Arizona, USA, from August 2005 to August 2008. We tested serum samples for evidence of exposure to 10 feline viruses: Feline Calicivirus (FCV), Feline Herpesvirus, Feline Enteric Coronavirus, Feline Syncytial Virus–Feline Foamy Virus, Feline Infectious Peritonitis, Feline Immunodeficiency Virus, Feline Panleukopenia Virus (FPLV), Feline Leukemia Virus, Canine Distemper Virus (CDV), and Toxoplasma gondii. The highest prevalences of exposure were: T. gondii (8/9), FPLV (7/9), and FCV (6/9). One male was seropositive for CDV, T. gondii, and FPLV. Mountain lions inhabiting smaller fragmented landscapes and urban areas have more contact with other felids and domesticated animals. Frequent contact among mountain lions, other felids, and domesticated animals can lead to higher risk of exposure and facilitate the spread of the disease from animal to animal. © 2012 The Wildlife Society.